Production of biosurfactant from biodiesel side-stream glycerine by Pseudomonas aeruginosa RS6 - Baskaran, Shobanah Menon (2020)
Biosurfactant is an amphipathic compound produced by microorganisms as a secondary metabolite. Since biosurfactants are biologically produced compounds that have been shown to be less harmful to the environment, biodegradable, and safe as opposed to conventional synthetic surfactants because they can be produced from renewable substrates. Biosurfactants showed an efficient and successful application in numerous industries such as in agriculture (biopesticide), medical (antimicrobial agent) and washing industry (cleaning agent). Waste glycerine is a by-product of the biodiesel industry, and the current glycerol market is unable to accommodate the excess amounts produced; as a result, new markets for refined glycerol must be developed. This study aims to obtain the optimized fermentation condition for the production of rhamnolipids biosurfactant by Pseudomonas aeruginosa RS6 using waste glycerine as a substrate. In this study, the effect of temperature, initial pH medium, waste glycerine concentrations, nitrogen sources and nitrogen concentrations on the production of rhamnolipid biosurfactant was studied. The rhamnolipid produced was determined by high-performance liquid chromatography (HPLC) method, emulsification index, and surface tension measurement. Rhamnolipids produced under the optimized fermentation conditions were further characterized using liquid chromatography-mass spectrometry (LC-MS) and Fourier transform infrared spectrometry (FT-IR) and evaluated on the antimicrobial activity and toxicity of rhamnolipids produced by strain RS6 using selected pathogens to see the potential of using rhamnolipids in agricultural industry. The optimized conditions for the production of rhamnolipids was obtained when P. aeruginosa RS6 was grown in a basal salt medium at initial pH 6.5 supplemented with 1.0% waste glycerine (v/v) and 0.2 M sodium nitrate at 35°C. Moreover, the fermentation was carried out in a 2 L stirred tank bioreactor to see the difference in rhamnolipids production compared to in shake flask. About 2.72 g/L and 3.0 g/L of rhamnolipids were obtained from shake flask and stirred tank bioreactor, respectively. In the crude extract of biosurfactant obtained, FT-IR confirmed the presence of rhamnolipids and LC-MS confirmed the crude consists of both mono- and di-rhamnolipids. Rhamnolipids produced can inhibit the growth of both Gram-positive (Bacillus pumilus) and Gram-negative (Pantoea stewartii, Pantoea ananatis and Erwinia mallotivora) plant pathogens (ranging from 37% to 77% of inhibition) and showed low toxicity on fish embryonic toxicity test (91.67% of zebrafish survivals). Results obtained showed that waste glycerine from biodiesel industry could be used as a renewable carbon source for the production of rhamnolipids by P. aeruginosa RS6. The rhamnolipids produce can be applied in the agricultural industry as an antimicrobial agent to combat the pathogenic microorganisms causing diseases to plants.